Role of Adding Spironolactone and Renal Denervation in True Resistant Hypertension: One-Year Outcomes of Randomized PRAGUE-15 Study - Rosa, Ján; Widimský, Petr; Waldauf, Petr; Lambert, Lukáš; Zelinka, Tomáš; Táborský, Miloš; Branny, Marian; Toušek, Petr; Petrák, Ondřej; Čurila, Karol; Bednář, František; Holaj, Robert; et al. (Hypertension, 2016)
This randomized, multicenter study compared the relative efficacy of renal denervation (RDN) versus pharmacotherapy alone in patients with true resistant hypertension and assessed the effect of spironolactone addition. We present here the 12-month data. A total of 106 patients with true resistant hypertension were enrolled in this study: 52 patients were randomized to RDN and 54 patients to the spironolactone addition, with baseline systolic blood pressure of 159±17 and 155±17 mm Hg and average number of drugs 5.1 and 5.4, respectively. Twelve-month results are available in 101 patients. The intention-to-treat analysis found a comparable mean 24-hour systolic blood pressure decline of 6.4 mm Hg, P=0.001 in RDN versus 8.2 mm Hg, P=0.002 in the pharmacotherapy group. Per-protocol analysis revealed a significant difference of 24-hour systolic blood pressure decline between complete RDN (6.3 mm Hg, P=0.004) and the subgroup where spironolactone was added, and this continued within the 12 months (15 mm Hg, P= 0.003). Renal artery computed tomography angiograms before and after 1 year post-RDN did not reveal any relevant changes. This study shows that over a period of 12 months, RDN is safe, with no serious side effects and no major changes in the renal arteries. RDN in the settings of true resistant hypertension with confirmed compliance is not superior to intensified pharmacological treatment. Spironolactone addition (if tolerated) seems to be more effective in blood pressure reduction.
Keywords: echokardiografie; Kidney; vztah mezi dávkou a účinkem léčiva; hypertenze; Drug Resistance; Female; výsledek terapie; ženské pohlaví; Tomography, X-Ray Computed; léková rezistence; Time Factors; časové faktory; lidé; Sympathectomy; Blood Pressure Monitoring, Ambulatory; Treatment Outcome; následné studie; Echocardiography; krevní tlak; Humans; Middle Aged; Dose-Response Relationship, Drug; prospektivní studie; sympatektomie; Follow-Up Studies; Hypertension; Male; Prospective Studies; ambulantní monitorování krevního tlaku; Diuretics; diuretika; lidé středního věku; mužské pohlaví; angiografie; Blood Pressure; ledviny; Spironolactone; spironolakton; Angiography; počítačová rentgenová tomografie